Designing a blueprint for Theoretical assessment of community medicine phase III Indian Medical Graduates - Yadav, Aradhana; Kaur, Samarjeet; Barman, Santosh Kumar; Sonam (Indian Journal of Community Health, 2025)
Introduction: A blueprint serves as a high-quality, standardized document that encapsulates all instructional resources and the outcomes they have produced. It ensures that every aspect of the curriculum and its instructional domains is thoroughly addressed during the review process. Objective: To create blueprints for the undergraduate community medicine exam curriculum. Material & Method: The distribution of various question types (MCQ, SAQ, and LAQ) and cognitive domain levels (recall, understanding, and application) is proportionally allocated. The impact point (I) ranges from 1 to 3, and the frequency score also ranges from 1 to 3. The weightage coefficient (W) is calculated using the formula I × F / T. Result: The total of all I × F for Paper I amounts to 44, while for Paper II, it totals 43. Blueprints for Community Medicine Paper I and Paper II are each worth 100 marks. Conclusion: Our study's findings indicate that the topics "Principles of Health Promotion and Education," "Occupational Health," "Epidemiology of Communicable Diseases," "Demography and Vital Statistics," and "Health Care of the Community" collectively represent more than half of the total weightage.